2005
DOI: 10.1124/jpet.105.091926
|View full text |Cite
|
Sign up to set email alerts
|

Improved Bioavailability of the mGlu2/3 Receptor Agonist LY354740 Using a Prodrug Strategy: In Vivo Pharmacology of LY544344

Abstract: Numerous studies have indicated that selective agonists of group II metabotropic glutamate (mGlu) receptors, such as LY354740 [(1S,2S,5R,6S)-2-aminobicyclo[3.1.0]hexane-2,6-dicarboxylate monohydrate] and LY379268 [(Ϫ)-2-oxa-4-aminobicyclo[3.1.0]hexane-4,6-dicarboxylate], may be useful in the treatment of many psychiatric disorders, including psychosis, anxiety, and drug withdrawal. Although animal and human studies demonstrate potential therapeutic utility, poor oral bioavailability is a limiting factor in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
30
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 28 publications
5
30
1
Order By: Relevance
“…There were no reports of convulsions or other neurobehavioral adverse events. Plasma concentrations of LY354740 were comparable to those previously associated with efficacy in GAD (data on file, Eli Lilly and Co.), confirming the utility of using a dipeptide analog to increase the oral bioavailability (by way of peptide transporters) of otherwise poorly absorbed amino-acid analogs such as LY354740 (Bueno et al, 2005;Rorick-Kehn et al, 2006). The use of the prodrug LY544344 is associated with increased oral bioavailability and decreased variability of active moiety (LY354740) in plasma concentration.…”
Section: Ly354740 Plasma Concentrationssupporting
confidence: 68%
See 1 more Smart Citation
“…There were no reports of convulsions or other neurobehavioral adverse events. Plasma concentrations of LY354740 were comparable to those previously associated with efficacy in GAD (data on file, Eli Lilly and Co.), confirming the utility of using a dipeptide analog to increase the oral bioavailability (by way of peptide transporters) of otherwise poorly absorbed amino-acid analogs such as LY354740 (Bueno et al, 2005;Rorick-Kehn et al, 2006). The use of the prodrug LY544344 is associated with increased oral bioavailability and decreased variability of active moiety (LY354740) in plasma concentration.…”
Section: Ly354740 Plasma Concentrationssupporting
confidence: 68%
“…To improve LY354740 absorption and further assess the therapeutic effects of mGlu2/3 agonists, a pharmacologically inactive peptidyl prodrug (L-alanine) form of the active compound LY354740, named LY544344, was developed. LY544344 is absorbed in the gastrointestinal tract through active PEP T1 transport, with eventual hydrolysis to produce molar equivalents of LY354740 and L-alanine (Bueno et al, 2005;Rorick-Kehn et al, 2006). In rodents, oral administration of LY544344 is associated with at least 10-fold improvement in bioavailability compared with oral LY354740 and behavioral effects comparable to those seen with parenteral administration of LY354740 (Rorick-Kehn et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Early in vitro data demonstrated that LY544344 is chemically stable but susceptible to hydrolytic enzymes in jejunal homogenates (Bueno et al, 2005). Previous reports demonstrated that this combination of active absorption and rapid enzymatic hydrolysis results in a dramatic increase in the oral bioavailability of LY354740 in rats (Rorick-Kehn et al, 2006) and humans (Kellner et al, 2005). However, the doses at which these studies were conducted were relatively low.…”
Section: Discussionmentioning
confidence: 87%
“…1), emerged from this, based on its active transport and activation profiles. LY544344 has relatively high affinity for hPepT1, is rapidly hydrolyzed in human jejunum and liver homogenates, and displays dramatically improved bioavailability and pharmacologic activity in rodents (Rorick-Kehn et al, 2006). The present experiments were conducted with LY544344 to further elucidate the first-pass activation process and to evaluate dose proportionality in nonclinical species.…”
mentioning
confidence: 99%
“…However, the clinical development of LY354740 has been hampered by low oral bioavailability, due to minimal absorption in the gastrointestinal tract and inadequate penetration through the blood-brain barrier (Johnson et al, 2002;Bueno et al, 2005). Although recent attempts to improve the oral bioavailability of this compound have met with good success (Rorick-Kehn et al, 2006), further research has been devoted to discovering additional potent and selective mGlu2/3 receptor agonists. Herein, we report the in vitro pharmacological profile and pharmacokinetic properties of the structurally novel mGlu2/3 receptor agonist (Ϫ)-(1R,4S,5S,6S)-4-amino-2-sulfonylbicyclo[3.1.0]hexane-4,6-dicarboxylic acid (LY404039) (Fig.…”
mentioning
confidence: 99%